1980
DOI: 10.1002/jcc.540010402
|View full text |Cite
|
Sign up to set email alerts
|

Small elemental clusters. I. The structures of Be2, Be3, Be4, and Be5

Abstract: The geometries and energies of beryllium clusters up to Be5 are examined using ab initio molecular orbital theory. Allowances are made for electron correlation with MBller-Plesset perturbation theory to fourth order. Correlation is found to have a dramatic effect on the relative energies of the several structures examined for Be4 and Bes. Furthermore, the effect of d-type basis functions on the correlation energy results in an increased binding energy for the clusters. Be2 is only weakly bound. For Be:i, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 54 publications
5
24
0
Order By: Relevance
“…The bond distances and total energies are consistent with earlier theoretical studies [8][9][10][11][12][13][14][15][16][17][18][19]. The theoretical frequencies in Table 2 do not fit this formula well a result which is not surprising when one realizes that the CFA amounts to neglecting all off-diagonal elements in the internal coordinate force constant matrix.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The bond distances and total energies are consistent with earlier theoretical studies [8][9][10][11][12][13][14][15][16][17][18][19]. The theoretical frequencies in Table 2 do not fit this formula well a result which is not surprising when one realizes that the CFA amounts to neglecting all off-diagonal elements in the internal coordinate force constant matrix.…”
Section: Resultssupporting
confidence: 85%
“…Previous theoretical research has shown [14,17,19] that the reliable prediction or the dissociation energy of Be 4 , namely 6E(Be 4 + 4Be), requires a high level of theory. Specifically, d orbitals must be included in the basis set, and the effects of electron correlation must be carefully considered.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various metal clusters that have been investigated theoretically, probably beryllium clusters of varying size have been studied most extensively (14)(15)(16)(17)(18)(19)(20)(21). The, smallest system, Be2, has been used as a model in theoretical studies since 1931 (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…The, smallest system, Be2, has been used as a model in theoretical studies since 1931 (22,23). The potential energy curve of the ground state of Be2 has been the subject of a number of theoretical investigations (14)(15)(16)(17)(18) but in spite of the large number of calculations with various degrees of sophistication, it was only recently that reliable calculations on the potential energy curve for the ground state of Be2 have Feen reporte$ (14,16,17). The calculated values of Re = 2.51 A (16), 2.50A (17) and D, = 2.23-2.34kcal/mol (14), 2.04 k 0.2kcal/mol (17) are in good agreement with the experimentally determined values of Re = 2.465 A, and D, = 2.29 kcal/mol (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%